Determination of the parameters of multi-carrier spectrum in CdHgTe. II. Discrete mobility spectrum analysis - Izhnin, Igor I.; Voytsekhovskiy, Alexander V.; Korotaev, Alexander G.; Mynbaev, Karim D. (Russian physics journal)
The paper, which consists of two parts, considers in detail the method of discrete mobility spectrum analysis (DMSA) proposed by the authors as well as its application to determine the parameters of charge carriers in CdHgTe. The first part of the work was a brief review of the existing methods for analyzing the field dependences of the Hall coefficient and conductivity in structures with a multi-carrier spectrum of charge carriers. In the second part of the work, the physical properties of the mobility spectrum envelope in the mobility spectrum analysis (MSA) method are analyzed and the main idea, features, and algorithm of the DMSA method are presented. On the example of studying the electrical properties of numerous samples of CdHgTe epitaxial films, the high sensitivity of the DMSA was confirmed. Using DMSA, we analyzed a number of dependences of the conductivity tensor components σxx and σxy on the magnetic field B, available in the literature, and compared the results of the analysis with those obtained with other methods.